Closed-Loop Supply Chain: A bibliometric and visualization analysis - Saher, Liudmyla; Syhyda, Liubov; Korobets, Olena; Berezyanko, Tamara (My University, 2021)
Nowadays, enterprises have to be good for society, to take care of the environment, and to achieve profit at the same time. And the closed-loop supply chain helps them being so. However, there is a lack of bibliometric and visualization research in the area of “Closed-Loop Supply Chain”. Thus, this research aims to present a bibliometric overview to define the current state of scientific production regarding “Closed-Loop Supply Chain”. The review of 807 publications from the Scopus database (1995–2020) was conducted. Two combinations of words with the logical operator (“supply chain” AND “reverse logistics”) were used. The “title, abstract, keywords” field of search in the Scopus database was done. The visualization of the results was made using VOSviewer program to graphically map the material. The study used the co-occurrence of keywords and co-authorship (country) analyses. As a result, the most productive authors and journals were defined. The most cited studies were determined. Country clusters and keywords (co-occurrence) clusters were represented. The obtained results of the analysis and graphical presentations are relevant, and they form the basis for a better understanding of the concept of Closed-Loop Supply Chain.
Keywords: замкнутий ланцюг постачання; Scopus; наукова продукція; підприємство; closed supply chain; scientific products; enterprise; кафедра економіки праці та менеджменту